The influence of theoretical concepts of the structure of the film on the development of cinema critic - Sayenkova-Melnitskaya, Ludmila P. (Journal of the Belarusian State University. Journalism, 2019)
The article generalizes the experience of theoretical research in the field of analysis of artistic expression of the movie.  Presents the practice of referring to methodological issues of the cinema critic of the famous soviet filmmakers. Discusses the  pattern of development of the cinema critic reflection on the principles of representation of the film. Explains the influence  of different methodological concepts (linguistic, semiotic, and systemic – integritive analysis) on the formation of analytical  tools in the critic. The necessity of analytic principle in the presentation of works of cinema in mass media.
Keywords: cinema critic; analysis; film; method; mass media